2014
DOI: 10.4196/kjpp.2014.18.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of C18 Fatty Acids on Intracellular Ca2+Mobilization and Histamine Release in RBL-2H3 Cells

Abstract: To investigate the underlying mechanisms of C18 fatty acids (stearic acid, oleic acid, linoleic acid and α-linolenic acid) on mast cells, we measured the effect of C18 fatty acids on intracellular Ca2+ mobilization and histamine release in RBL-2H3 mast cells. Stearic acid rapidly increased initial peak of intracellular Ca2+ mobilization, whereas linoleic acid and α-linolenic acid gradually increased this mobilization. In the absence of extracellular Ca2+, stearic acid (100 µM) did not cause any increase of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…According to the previous study [ 26 ], Human neuroblastoma SH-SY5Y cells were cultured at 37 °C in Dulbecco’s modified Eagle’s medium (DMEM) supplemented with 10% FBS which was inactivated by heat in a humidified 95% air, 5% CO 2 incubator. The cells were transferred to low serum media (10% FBS) for two hours before the treatment with BF-7.…”
Section: Methodsmentioning
confidence: 99%
“…According to the previous study [ 26 ], Human neuroblastoma SH-SY5Y cells were cultured at 37 °C in Dulbecco’s modified Eagle’s medium (DMEM) supplemented with 10% FBS which was inactivated by heat in a humidified 95% air, 5% CO 2 incubator. The cells were transferred to low serum media (10% FBS) for two hours before the treatment with BF-7.…”
Section: Methodsmentioning
confidence: 99%
“…Oleic acid ( 6 ) was reported to weakly inhibit histamine and beta-hexosaminidase release by antigen- and A23187-induced RBL-2H3 cells [47, 48]. In addition, oleic acid only slightly increased intracellular Ca 2+ that induced cell degranulation [49]. In an in vivo study, peanuts containing high oleic acid was also found to be less allergenic than normal peanuts [50].…”
Section: Discussionmentioning
confidence: 99%